2005
DOI: 10.1088/0031-9155/50/22/009
|View full text |Cite
|
Sign up to set email alerts
|

Transaxial system models for jPET-D4 image reconstruction

Abstract: A high-performance brain PET scanner, jPET-D4, which provides four-layer depth-of-interaction (DOI) information, is being developed to achieve not only high spatial resolution, but also high scanner sensitivity. One technical issue to be dealt with is the data dimensions which increase in proportion to the square of the number of DOI layers. It is, therefore, difficult to apply algebraic or statistical image reconstruction methods directly to DOI-PET, though they improve image quality through accurate system m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 17 publications
1
33
0
1
Order By: Relevance
“…This high resolution was realized by reducing the LGSO crystal size to 1.44 路 1.44 路 4.5 mm, and the high light output of the LGSO enables discrimination of input signals from different crystals. The DOI information was effective at decreasing degradation in radial resolution due to parallax error (27). The effectiveness of DOI was also demonstrated in the human imaging.…”
Section: Discussionmentioning
confidence: 84%
“…This high resolution was realized by reducing the LGSO crystal size to 1.44 路 1.44 路 4.5 mm, and the high light output of the LGSO enables discrimination of input signals from different crystals. The DOI information was effective at decreasing degradation in radial resolution due to parallax error (27). The effectiveness of DOI was also demonstrated in the human imaging.…”
Section: Discussionmentioning
confidence: 84%
“…In our laboratory, a brain PET scanner, jPET-D4 [19,20], has been developed using four-layer DOI detectors to achieve a spatial resolution better than 2.5 mm within the FOV (transaxial, 312 mm; axial, 260 mm), and an absolute sensitivity higher than 10% at the center of the FOV. The four-layer encoding was achieved using a combination of Anger-logic and pulse shape discrimination; the upper and lower halves were discriminated by the reflector structure, and each half was a phoswich detector composed of two kinds of GSO crystals doped at the Ce concentrations of 0.5 mol% (decay time, 60 ns) and 1.5 mol% [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Further improvement in the benefits of resolution recovery reconstruction can also be achieved by combining this method with other hardware-driven advanced technologies, such as, those that provide DOI position measurements and TOF information [13,50]. In a recent study, Kadrmas et al [13] showed that when TOF information is utilized in conjunction with resolution recovery modeling, lesion detection performances are improved both in numerical and human observer tests as compared with either technique resolution recovery or TOF alone (Fig.…”
Section: Hybrid Approachesmentioning
confidence: 99%